Albanian Federation as a Peace Factor in the Region - Ramabaj, Sadri (European Journal of Multidisciplinary Studies, 2016)
The process of creating the Albanian Federation, respectively the acceleration level, is combined with the EU integration process, respectively disintegration process. Certainly, the process of creating the Albanian Federation, as a political project does not face with the challenges the European Political Union project is facing, but the approach to the EU challenges will make us more clear the process from where could be outlined the creation of Albanian Federation. Divergences between the new and older EU members, but also between the EU member states that have national heterogeneity and as consequence were not allowed to pass the Rubicon of internal self-determination, different ethnicities within national borders ( Spain, Romania, Cyprus, Slovakia and Greece ) with those who present the type of homogeneous state ( Germany, Italy, Sweden, Slovenia, etc.. ), are reflected in the attitude towards Kosovo and, generally, the right to self-determination. Comparative overview of theses of Applied Policy Research Center ( CAP, Muenchen ) on possible trends in the development of European integration processes, in relation to the process of creating Albanian Federation to the first and fifth scenario results to be small, while to the fourth scenario this possibility seems to be big. The fourth scenario, combined with elements of the second scenario, it seems to be exactly that, in current circumstances is considered the most probable to be realized, but that goes in favour of the creation process of the Albanian Federation. Creation of the Albanian Federation should be regarded as a contribution to sustainable peace in the region. Albanian Federation could play a positive role in deepening the transatlantic relationship